Physiotherapy Provision Following Discharge after Total Hip and Total Knee Replacement: A Survey of Current Practice at High‐Volume NHS Hospitals in England and Wales. (9th July 2012) - Artz, Neil; Dixon, Sam; Wylde, Vikki; Beswick, Andrew; Blom, Ashley; Gooberman‐Hill, Rachael
Abstract Background Total hip replacement (THR) and total knee replacement (TKR) are two common elective orthopaedic procedures, and the provision of physiotherapy for patients after discharge is variable, with evidence for best practice remaining uncertain. Aims and objectives To determine the standard physiotherapy service offered to patients following discharge after THR and TKR. Methods A telephone survey was carried with clinicians at 24 high‐volume NHS orthopaedic centres in England and Wales. Information was gathered on standard physiotherapy provision and categorized into; no routine physiotherapy, outpatient physiotherapy (including one‐to‐one and group), home‐based physiotherapy or other physiotherapy (including telephone consultation and drop‐in services). Results No centres surveyed referred patients to outpatient physiotherapy as a routine pathway of care following THR. Eleven centres provided group physiotherapy to patients after discharge following TKR compared with five centres providing one‐to‐one outpatient physiotherapy. Conclusion The provision of physiotherapy following discharge after TKR is a more common practice than after THR, where ongoing physiotherapy is provided depending upon clinical need. Group exercises are the favoured destination for patients following TKR in high‐volume centres. Copyright © 2012 John Wiley & Sons, Ltd.